The Analysis of Rhetorical Styles of World Figures in Public Speaking - Arianto, Tomi; Septriani, Septriani (Asosiasi Ide Bahasa Kepri, 2023)
This research aims to reveal various rhetorical styles of world figures when delivering their orations/speeches in front of the public from a language style perspective. This research uses a figurative language approach as a theoretical concept. Figurative language is language that